INFLUENCE OF ENDOTHELIAL CELLS PREINCUBATED WITH CYTOKINES ON THP-1 MONOCYTE-LIKE CELLS PHENOTYPE AND FUNCTIONS - E. A. Starikova (SPb RAACI, 2014)
Abstract. We demonstrated that TNFα, IFNγ and IL-4 induce different patterns of endothelial cells activation. The greatest alterations were observed in TNFα threated endothelial cells. Under the influence of this cytokine there was a statistically significant elevation of IL-8 and MCP-1 production by endothelial cells, of THP-1 adhesion and of migration toward endothelial cells monolayer. At the same time we had not observed any immunophenotype alteration of THP-1 cocultured with endothelial cells treated with TNFα.IFNγ и IL-4 induced statistically significant inhibition of THP-1 adhesion. IL-4 treated endothelial cells have elevated levels of IL-8 and MCP-1 production and stimulated THP-1 migrations. IFNγ showed inhibition of IL-8 and MCP-1 spontaneous production and THP-1migration.Incubation of THP-1 with untreated and IFNγ treated endothelial cells led to significant elevation of HLA-DR expression. Expression of CD68 was significantly higher in case of THP-1 cocultured with IL-4 treated endothelial cells. There was no any correlation between immunophenotype alteration THP-1cells and others parameters alteration.